Doubled lifespan and patient‐like pathologies in progeria mice fed high‐fat diet. Issue 1 (12th December 2018) - Kreienkamp, Ray; Billon, Cyrielle; Bedia‐Diaz, Gonzalo; Albert, Carolyn J.; Toth, Zacharie; Butler, Andrew A.; McBride‐Gagyi, Sara; Ford, David A.; Baldan, Angel; Burris, Thomas P.; Gonzalo, Susana
Abstract: Hutchinson‐Gilford Progeria Syndrome (HGPS) is a devastating premature aging disease. Mouse models have been instrumental for understanding HGPS mechanisms and for testing therapies, which to date have had only marginal benefits in mice and patients. Barriers to developing effective therapies include the unknown etiology of progeria mice early death, seemingly unrelated to the reported atherosclerosis contributing to HGPS patient mortality, and mice not recapitulating the severity of human disease. Here, we show that progeria mice die from starvation and cachexia. Switching progeria mice approaching death from regular diet to high‐fat diet (HFD) rescues early lethality and ameliorates morbidity. Critically, feeding the mice only HFD delays aging and nearly doubles lifespan, which is the greatest lifespan extension recorded in progeria mice. The extended lifespan allows for progeria mice to develop degenerative aging pathologies of a severity that emulates the human disease. We propose that starvation and cachexia greatly influence progeria phenotypes and that nutritional/nutraceutical strategies might help modulate disease progression. Importantly, progeria mice on HFD provide a more clinically relevant animal model to study mechanisms of HGPS pathology and to test therapies.